Kepadatan dan Kekuatan Tulang Sapi Bali Betina yang Dipelihara Masyarakat di Bali (THE DENSITY AND STRENGTH OF FEMALE BALI CATTLE BONE REARING BY BALINESE COMMUNITY) - Batan, I Wayan; Fanggidae, Betharia Criselda; Suatha, I Ketut; Suarsana, I Nyoman (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Bali cattle (Bos (Bibos) banteng) often experience fractures (fractures) of metacarpale, femur bone or tibia-fibular bone. This study was aim to reveal the strength and density of female Bali cattle bone which determines the occurrence of fractures. In order to reveal the strength of bali cattle bones, the elements that need to be explored include: bone density, cortical thickness of tibia bone, bone diameter, and bone resistance to pressure.  To determine bone density performed by measuring bone specific graavity, cortical thickness of bone, carried out by splitting the bone by sawing the tibia bone extensively, then measuring the thickness of the wall of the bone cylinder using a caliper.  Measurement of bone resistance to pressure was done by weighing the bone with a certain weight until the bone breaks or cracks and then measured by checking in which load the bones breaks or cracks. The result shown that the average density of Bali cow os tibia is 1.95 g/mL, average os tibia diameter is 26.45 mm, os tibia cortical thickness from top, middle, and bottom in sequence are 5.50 mm, 6.25 mm, and 5.35 mm. The result of os tibia compressive strength test is 9.26 Pascal with average load can be hold is 56.75 Newton and average wide of os tibia cross section cut is 6.05 cm2. This study result can be used as representation of Bali cow os tibia strength that has not been widely reported and can be used as recommendation for improvement of female Bali cattle livestock management.